Modeling Operational Transformation Strategies for Lean Fulfillment and Cost Reduction in Global E-Commerce Enterprises - Sharon Nwani; Olayinka Abiola-Adams; Bisayo Oluwatosin Otokiti; Jeffrey Chidera Ogeawuchi (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This paper develops a comprehensive operational transformation framework tailored for lean fulfillment and cost reduction in global e-commerce enterprises. It explores the evolution of e-commerce and its associated operational challenges, emphasizing the critical role of lean principles in managing competitive costs and enhancing service delivery. Key drivers such as demand volatility, supply chain complexity, technological advancements, and rising customer expectations are examined for their impact on operational dynamics. The study models lean fulfillment strategies through principles like just-in-time inventory management and streamlined order processing, complemented by workforce optimization and supplier collaboration. By integrating technology-enabled process improvements and fostering strategic procurement practices, enterprises can achieve sustainable cost efficiencies while maintaining high service standards. The framework underscores strategic implications for e-commerce businesses aiming to thrive in volatile markets and highlights future innovation pathways focused on sustainability, automation, and digital integration. Overall, the paper provides actionable insights to help firms achieve operational excellence and long-term competitive advantage.
Keywords: Lean fulfillment; operational transformation; cost reduction; global e-commerce; supply chain optimization; process automation